Experimental analysis to study the effect of perforated louvered strip‐coiled spring insert on heat transfer performance in a double pipe heat exchanger. Issue 4 (21st December 2021) - Kumar, Rajan; Chandra, Prakash
Abstract: Experiments have been conducted to study the effect of louvered strip‐coiled spring (PLSCS) turbulators having different pitches and the same angle of attack on thermal performance and pressure drop of a concentric tube heat exchanger. Two inserts in combined form were used for experimentation under turbulent flow at different Reynolds numbers ( Re ) ranging between 5000 and 20, 000. Two pitches (40 mm and 50 mm) of elliptical‐shaped perforated louvered strips (PLS) having the same angles of attack ( θ = 20 ° ) have been taken that were welded on the central core rod. Spring inserts have the same coil diameter of 12 mm with two varying pitches to achieve pitch ratios ( p s / d s ) of 0.5 and 1. Both heat transfer and pressure drop increase with a decrease in pitches of both LS and spring inserts. Nusselt number has the maximum value with spring of pitch 6 mm in combination with a PLS of 40 mm pitch at θ = 20 °, which is 130.75% higher than the plain tube at the lowest Re among the PLSCS inserts. With perforation, a slight increase in both Nusselt number and friction factor was observed. The maximum thermal performance efficiency value is 1.105 for the lowest Re value.